Perceptions assigned by nurses on the relationship between innovation and nursing (Research, Society and Development, 2021)
Objective: To describe the perceptions of nurse managers about the relationship between Nursing and innovation in the work process. Method: This is a quantitative, descriptive, exploratory study, carried out in a specialized oncology hospital, large, highly complex and philanthropic, located in the central region of the city of São Paulo-SP. Results: 54 nurses participated in the nursing administration work process. Respondents had a high perception of nursing and innovation. Representation in innovation in nursing is linked to the creation of materials and equipment. Discussion: Innovation is an important issue for the health scenario and is part of management and the work process, matured through teaching, continuing education and experience. Conclusions: Innovation, without a doubt, provides success to the health system and process and, therefore, the absence of an innovation method influences the lack of clarity in everyday life. causes the low or no appreciation of the theme in practice.